Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.2147/jhl.s225291
|View full text |Cite
|
Sign up to set email alerts
|

<p>Characteristics of Faculty at Risk of Leaving Their Medical Schools: An Analysis of the StandPoint™ Faculty Engagement Survey</p>

Abstract: This study seeks to identify the characteristics and attitudes of faculty in US medical colleges who are at risk of leaving their institution. Methods: This research leverages data from the AAMC StandPoint Faculty Engagement Survey administered to 37,779 faculty representing 36 institutions participating during 2013-2016. Univariate and multivariable robust logistic regression models were used to assess predictors of the intent to leave based on the question: "Do you plan to leave this medical school in the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
3
6
0
Order By: Relevance
“…Ineffective leadership and inadequate mentorship as major themes are consistent with prior research, both in PA education [11][12][13][14][15] and in academic medicine. 17,[29][30][31][32][33] The theme of erroneous expectations of academic work is also consistent with a description of expectancy theory in the higher education literature. 34 Previous research on PA faculty has emphasized the importance of organizational support, clear expectations for work, and experienced leadership to guide and mentor faculty.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Ineffective leadership and inadequate mentorship as major themes are consistent with prior research, both in PA education [11][12][13][14][15] and in academic medicine. 17,[29][30][31][32][33] The theme of erroneous expectations of academic work is also consistent with a description of expectancy theory in the higher education literature. 34 Previous research on PA faculty has emphasized the importance of organizational support, clear expectations for work, and experienced leadership to guide and mentor faculty.…”
Section: Discussionsupporting
confidence: 84%
“…Ineffective leadership and inadequate mentorship as major themes are consistent with prior research, both in PA education 11-15 and in academic medicine. 17,29-33 The theme of erroneous expectations of academic work is also consistent with a description of expectancy theory in the higher education literature. 34…”
Section: Discussionsupporting
confidence: 76%
“…Academic medical centers may facilitate faculty growth through offerings like formal mentoring for career and leadership development and executive coaching to help faculty strategize their desired career advancement. Indeed, Zimmerman et al 18 found that receiving professional development opportunities, appreciation from supervisors, or a daily sense of accomplishment were key factors in faculty engagement. But, ultimately the impact of organizational efforts is only as effective as their alignment with the values of the faculty.…”
Section: Discussionmentioning
confidence: 99%
“…Some data suggest that faculty development programs may increase career satisfaction and engagement, utilization and satisfaction with mentorship opportunities, research productivity, and promotion rates [5][6][7][8][9][10] . Indeed, faculty who participate in professional development are more fulfilled, productive, and are less likely to leave their institution 5,[11][12][13][14]15 . Mentoring programs have been identified as particularly impactful at promoting faculty vitality; however, mid-career and senior clinical faculty may not have the knowledge base and mentoring skills to provide impactful guidance 9,16 and the optimal approach to mentor training and its effects on the mentor's career development and professional vitality are not known.…”
Section: Introductionmentioning
confidence: 99%